Reclaiming agency in instructional technology integration: a praxeological analysis of pre-service mathematics teachers' roles in a GeoGebra-based model lesson - Mensah, Farouq Sessah (Frontiers in Education, 2025)
The integration of instructional technology in mathematics teacher education is often guided by demonstration-based approaches that centralize authority and limit opportunities for Pre-Service Teachers (PSTs) to engage meaningfully with pedagogical decision-making. Such practices risk reducing instructional technology integration to performance rather than empowering future educators to develop techno-didactic competence. This study critically examines how a GeoGebra-based model lesson shaped PSTs' experiences of participation, agency, and learning. It investigates the extent to which the instructional design enabled or constrained the development of autonomous techno-didactic praxeologies. A qualitative case study design was employed, drawing on video observations of a model lesson and a subsequent focus group interview with PSTs. The analysis used a dual-layered coding strategy grounded in the Anthropological Theory of the Didactic (ATD), combining deductive praxeological coding (tasks, techniques, technologies, and theory) with inductive thematic analysis of emergent constraints and expressions of agency. The results reveal a tightly controlled didactic contract that limited PSTs' engagement with the epistemic justifications underlying teaching decisions. While the model lesson effectively demonstrated the use of GeoGebra, it positioned PSTs as passive observers rather than co-constructors of knowledge. However, retrospective reflections showed emerging critical awareness and imagined alternatives to the instructional structure, indicating latent forms of agency shaped by constraint rather than enactment. The study highlights the need for teacher education practices that move beyond transmission to foster reflective, participatory, and design-oriented engagement with instructional technology. Implications point to a dual need: investment in material infrastructure and a reconfiguration of pedagogical routines that legitimize PSTs' agency. Future research should explore structured interventions that support the co-construction of techno-didactic knowledge through iterative, reflective practice.